Impact of parental history of substance use disorders on the clinical course of anxiety disorders - Moskowitz Amanda T; Hargraves Eric L; Rodriguez Benjamin F; Rende Richard; Pagano Maria E; Keller Martin B (BMC, 2007)
Abstract Background Among the psychological difficulties seen in children of parents with substance use problems, the anxiety disorders are among the most chronic conditions. Although children of alcoholic parents often struggle with the effects of parental substance use problems long into adulthood, empirical investigations of the influence of parental substance use disorders on the course of anxiety disorders in adult offspring are rare. The purpose of this study was to examine prospectively the relationship between parental substance use disorders and the course of anxiety disorders in adulthood over the course of 12 years. Methods Data on 618 subjects were derived from the Harvard/Brown Anxiety Research Project (HARP), a longitudinal naturalistic investigation of the clinical course of multiple anxiety disorders. Kaplan-Meier survival estimates were used to calculate probabilities of time to anxiety disorder remission and relapse. Proportional hazards regressions were conducted to determine whether the likelihood of remission and relapse for specific anxiety disorders was lower for those who had a history of parental substance use disorders than for individuals without this parental history. Results Adults with a history of parental substance use disorders were significantly more likely to be divorced and to have a high school level of education. History of parental substance use disorder was a significant predictor of relapse of social phobia and panic disorders. Conclusion These findings provide compelling evidence that adult children of parents with substance use disorders are more likely to have relapses of social phobia and panic disorders. Clinicians who treat adults with anxiety disorders should assess parental substance use disorders and dependence histories. Such information may facilitate treatment planning with regards to their patients' level of vulnerability to perceive scrutiny by others in social situations, and ability to maintain a long-term panic-free state.